A pilot study of cancer patients’ use of traditional healers in the radiotherapy department, University College Hospital, Ibadan, Nigeria. (2015)
Objective: This descriptive cross-sectional study assessed cancer patients’ use of traditional healers, the association between delay in coming to this clinic and patients’ use of traditional healers, reasons cancer patients use western medicine after trying traditional treatment and the cost of obtaining traditional treatment. Methods: Participants were made of 400 consecutive and consenting new patients in the Department of Radiotherapy, University College Hospital (UCH), Ibadan. A validated interviewer-administered semi-structured questionnaire was used for data collection. Data was analyzed using descriptive and inferential statistics. Focus group discussions were held with some of the clients as well as the traditional healers. Results: It showed that 34.5% of the patients patronized traditional healers, while 65.5% used only hospitals. The most common reason given among patients who patronized traditional healers for doing so was their desire to be healed and to be rid of pains (45.9%), while the most common reason they opt for western medicine afterwards was lack of improvement in their health condition (70.1%). The cost of traditional treatment for cancer ranged between no cost to N5,000 (that is approximately $31.25 @ $1 = N160) to be treated. The cost of orthodox care would range from a minimum of N40,000 to several millions of naira. Conclusions: Patients patronize traditional healers to be rid of pains; hence physicians should endeavor to control cancer-related symptoms, especially pains as the patients await diagnosis. Also, the low cost of obtaining traditional treatment, regular assurance of cure and other assistances given to them, could be an enticing factor in its use.